(untitled) (The Role of Exact Sciences in the Era of Modern Development, 2024)
In this article the features of using video materials in foreign language lessons is discussed. Furthermore, the use of video materials activates the attention and sparks interest among students in learning a foreign language is emphasized. An example of working with English-language video material is provided in the article.